2016
DOI: 10.1016/j.hgmx.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis: A multidisciplinary approach based on medical, social and demographic factors in a developing country

Abstract: Please cite this article in press as: Puente-Espel J, et al. Craniosynostosis: A multidisciplinary approach based on medical, social and demographic factors in a developing country. Rev Med Hosp Gen Méx. 2016. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…Additionally, Table 1 , Table 1 continue, Table 1 -1 continue presents the general characteristics of the studies included in this scoping review. The majority of the articles were narrative reviews/guidelines; only three publications were original investigations, including one retrospective cohort study ( 9 ), one case-control study ( 6 ), and one descriptive/exploratory study ( 15 ). Only one study ( 2 ) mentions in detail the main oral features/dental manifestations reported in pediatric patients with NSCS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Table 1 , Table 1 continue, Table 1 -1 continue presents the general characteristics of the studies included in this scoping review. The majority of the articles were narrative reviews/guidelines; only three publications were original investigations, including one retrospective cohort study ( 9 ), one case-control study ( 6 ), and one descriptive/exploratory study ( 15 ). Only one study ( 2 ) mentions in detail the main oral features/dental manifestations reported in pediatric patients with NSCS.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions lead to compensatory brain expansion into regions of the cranial vault that are not affected by CS, causing a cranial progressive deformity ( 5 , 12 ). Thus, there are different types of NSCS-characteristic dysmorphic head shapes with specific clinical findings, depending on the number of sutures fused and the involved regions ( 12 , 15 ). Single suture synostosis most frequently affects the sagittal suture, followed by the coronal, metopic, and lamboid sutures ( 3 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations